Electrochemistry, Electrochromic and Color Memory Properties of Polymer/Copolymer Based on Novel Dithienylpyrrole Structure. (1st March 2017) - Dai, Yuyu; Li, Weijun; Qu, Xingxing; Liu, Jin; Yan, Shuanma; Ouyang, Mi; Lv, Xiaojing; Zhang, Cheng
Highlights: A novel dithienylpyrrole derivative was designed and synthesized. The pTPhSNS and pTPhSNS-EDOT polymers by eletrochemical polymerization possess similar cross-linked structure. The introduction of EDOT into TPhSNS by copolymerization maybe help to form the expected cross-linked polymer structure with excellent electrochromic properties. Both pTPhSNS homopolymer and pTPhSNS-EDOT copolymers exhibit the electrochromic color memory behavior with excellent color stability at the oxidative state. Abstract: A new dithienylpyrrole derivative, namely terphenyl bridged-di[2, 5-di (2-thienyl)-1H-pyrrole] (TPhSNS), was designed and synthesized, then it was further prepared into cross-linked polymer (pTPhSNS) or copolymer (pTPhSNS-EDOT) with 3, 4-ethylenedioxythiophene (EDOT) via electrochemical polymerization. The cyclic voltammetry curves show that both the obtained pTPhSNS polymer and pTPhSNS-EDOT copolymer possess the excellent reversible oxidative properties. The UV–vis absorption spectra of pTPhSNS-EDOT at neutral state exhibits the similar character to pTPhSNS with very little redshift observed. After being applied at the positive voltage, the pTPhSNS-EDOT copolymers present a grey-blue color at the oxidation state, which is also close to the grey color of pTPhSNS (oxidized). Surprisingly, the pTPhSNS-EDOT copolymers exhibit the faster coloring time of 0.58 s and discoloring time of 0.38 s (at 1100 nm) compared with the pTPhSNS homopolymer films. Besides, the copolymers present a reasonable optical contrast of 40% (1100 nm). These results indicate that the introduction of EDOT into TPhSNS by copolymerization maybe help to form the expected cross-linked polymer structure with excellent electrochromic properties. Interestingly, both pTPhSNS and pTPhSNS-EDOT films present the electrochromic color memory behavior with excellent color stability at the oxidative state. The excellent electrochromic properties and color memory behavior enable TPhSNS with great potential applications in electrochromic area.